2017
DOI: 10.2219/rtriqr.58.4_298
|View full text |Cite
|
Sign up to set email alerts
|

<b>Frontal Obstacle Detection Using Background Subtraction and Frame Registration</b>

Abstract: Hiroki

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Yong [ 9 ] used machine vision to detect obstacles at railway crossings. Ryuta [ 25 ] proposed a method using a monocular camera and image processing for obstacle detection. For the methods that are based on image processing or conventional machine-learning techniques, it is difficult to design a unified method to detect and recognize various objects simultaneously.…”
Section: Related Workmentioning
confidence: 99%
“…Yong [ 9 ] used machine vision to detect obstacles at railway crossings. Ryuta [ 25 ] proposed a method using a monocular camera and image processing for obstacle detection. For the methods that are based on image processing or conventional machine-learning techniques, it is difficult to design a unified method to detect and recognize various objects simultaneously.…”
Section: Related Workmentioning
confidence: 99%
“…Sriwardene et al [18] proposed a smart driver assisting system, which could detect obstacles in the rail area. Nakasone et al [19] proposed a railway intrusion detection algorithm using a monocular camera and background subtraction. An image processing method including subtraction, binarization, morphological transformation and segmentation was used to track down moving obstacles at the level crossing [20].…”
Section: Related Work Of Railway Clearance Intrusion Detectionmentioning
confidence: 99%
“…The following technologies are being developed as they are essential for realizing the train operation control system shown in Fig. 1: 1) algorithms for safely controlling trains based on detailed information on train positions and the conditions of facilities and other components; 2) technologies [8] for collecting detailed transport information in real time to predict train operation; and 3) technologies to automatically calculate train operation plans in real time based on the prediction (Fig. 2).…”
Section: New Train Operation Control System Based On Detailed Positiomentioning
confidence: 99%
“…Using machine learning tech-nology, the system was also tried on humans. In the trial, the system was found to be capable of, depending on lighting conditions, detecting humans as far as 250 m ahead and had a detection rate of 90% or more for humans as far as 180 m ahead [8].…”
Section: Frontal Obstacle Detection Using Integrated Sensorsmentioning
confidence: 99%